Effects of polyphenols on doxorubicin‐induced oral keratinocyte cytotoxicity and anticancer potency against oral cancer cells. (19th February 2018) - Sheng, Hong; Ogawa, Toru; Niwano, Yoshimi; Sasaki, Keiichi; Tachibana, Katsuro
Abstract : Background: Normal human oral keratinocytes are highly sensitive to anticancer drugs including doxorubicin. Resveratrol, epigallocatechin gallate, and tannic acid are polyphenolic compounds that were reported to have cardioprotective effect when combined with doxorubicin. However, it is unknown whether these polyphenols could protect normal human oral keratinocytes against doxorubicin‐induced cytotoxicity without weakening its cytotoxic potential against oral cancer cells. Here, we examined the effects of the 3 polyphenolic compounds on doxorubicin‐induced cytotoxicity in normal human oral keratinocytes and also investigated their effects on doxorubicin potency in HSC‐2 human oral squamous cell carcinoma cells. Methods: Cell viability was evaluated, followed by the analysis of apoptosis and necrosis. The changes in intracellular reactive oxygen species at the early stage after treatment were also examined. Results: The results revealed that resveratrol in combination with doxorubicin additively augmented doxorubicin cytotoxicity in both types of cells. However, epigallocatechin gallate and tannic acid at a certain concentration mitigated the doxorubicin‐induced keratinocyte toxicity mainly due to reduced doxorubicin‐induced necrosis in normal human oral keratinocytes without weaken doxorubicin anticancer efficacy. The exact mechanism is still unknown but intracellular reactive oxygen species might be not the sole factor. Conclusions: This study for the first time reported the effects of resveratrol, epigallocatechin gallate, and tannic acid on doxorubicin‐induced cytotoxicity in normal oral keratinocytes and oral cancer cells. The combined use of epigallocatechin gallate or tannic acid with doxorubicin at a certain concentration could mitigate doxorubicin‐induced keratinocyte cytotoxicity without weakening doxorubicin anticancer efficacy.